Characteristics of Biodegradable Plastic From Cassava Starch With α-Cyclodextrin Based On Chitosan And Glycerol Composition - Purwanti, Oktavia Tri; Shabrina, Alifa Nur; Dermawan, Bagas; Insani, Reza Kautsar (Journal of Vocational Studies on Applied Research, 2024)
Plastic waste is one of the big problems in Indonesia. Plastic cannot be decomposed and is degraded by microorganisms. Therefore, research is needed on plastic materials that can be broken down, which is biodegradable plastic. Biodegradable plastic can be made from tuber materials such as cassava starch and chitosan composites which are easily degraded by microorganisms. The addition of α -cyclodextrin and glycerol is expected to add flexibility and elasticity to biodegradable plastic. At the stage of making biodegradable plastic, biodegradable plastic material is made by using a blending method and dried at an oven temperature of 50°C for 20 hours. The main ingredients of biodegradable plastic are cassava starch 0,65 gram and α -cyclodextrin 3,25 gram. Additional ingredients are glycerol (1; 1,5; and 2) mL and chitosan (1,3; 1,35; and 1,4) grams. The characteristics of biodegradable plastic were carried out by FTIR analysis, tensile strength test, elongation test, and biodegradable test. Biodegradable plastic test results for optimal tensile strength values for 1 mL glycerol and 1,4 gram chitosan were found to be 5,26 Mpa. The optimal percent elongation test results were 131, 7% for 1,5 mL glycerol and 1,3 gram chitosan. In the biodegradation test, biodegradable plastic was degraded on the 7 days.